Aerosolization inhalation of non-typeable Haemophilus influenzae outer membrane vesicles contributing to neutrophilic asthma - Zhang, Ying; Wang, Hongbo; Zhang, Yanqiu; Zhao, Peiliang; Li, Yanan (Frontiers in Microbiology, 2023)
Background: Neutrophilic asthma is poorly responsive to corticosteroids, and the mechanism underlying its pathogenesis remains unclear. Non-typeable Haemophilus influenzae (NTHi) is the most common bacterium found in induced sputum from patients with neutrophilic asthma. NTHi can release outer membrane vesicles (OMVs), which transfer biomolecules to host cells and the external environment. However, the role and mechanisms of NTHi OMVs in the pathogenesis of neutrophilic asthma remain unclear. Methods: We conducted assays to investigate whether NTHi OMVs can induce neutrophilic asthma when inhaled. We isolated and purified NTHi OMVs and administered them via a nebulizer to ovalbumin (OVA)-sensitized mice. We collected and sequenced serum, blood, bronchoalveolar lavage fluid, and lung tissue from each group and gathered lung function data. Results: Inhaled NTHi OMVs-induced neutrophilic asthma in OVA-sensitized mice. High-throughput sequencing revealed that NTHi OMV inhalation in OVA-sensitized mice significantly enriched inflammatory and immune-related signaling pathways. We found increased transcription and secretion of interleukin (IL)-1β and IL-17, which may contribute to neutrophilic asthma. Furthermore, we discovered that airway epithelium is the first receptor cell of NTHi OMVs and releases IL-1β. These findings suggest that NTHi OMVs could be a potential target for neutrophilic asthma therapy.